Analysis of Potentials and Strategies of Tourism Development at Mount Telomoyo - Doriani Lingga (EKO-REGIONAL, 2018)
Mount Telomoyo does not only have agricultural potential, but also tourism potential. However, this potential has not been developed optimally. This research aimed to analyze the tourism potential at Mount Telomoyo and formulate its development strategies, so that it becomes a region with fast growing economy. The method used in this research was Delphi and AHP analysis methods in strategy formulation. The potentials of nature tourism at Mount Telomoyo are Sekar Langit Waterfall, Seloprojo Waterfall, Bleder Lake, and Andong Mountain Climbing. The cultural tourism includes Umbul Temple Hot Pool, Sunan Geseng Tomb, and the cultural events such as traditional ceremony/Tradition and People’s Art. The locations of development priority were Seloprojo Tourism Area and Pandean Tourist Village. The development strategies of Telomoyo area as a global tourism included the construction of adequate road infrastructure, so that accessibility and mobility in Telomoyo area can run well. In addition, there was a need for the construction of supporting facilities and infrastructures, buildings and environmental arrangement, tourism and culture promotion using print and electronic media and involving stakeholders in the development and promotion, and socialization to the community about tourism.Keywords: Tourism, Potential, Strategy.